DEVELOPING LEADERSHIP POTENTIAL OF STUDENTS OF THE DIRECTION "ADVERTISING AND PUBLIC RELATIONS" TO ADAPT TO PROFESSIONAL ACTIVITIES - Elena Yu. Dvoinikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article discusses the techniques and strategy of the actualization of leadership potential of students of the direction "advertising and public relations." The relationship of the features of social and psychological adaptation to the efficiency of performing educational and professional tasks is analyzed. The importance of incorporating the leadership potential of students in the process of finding solutions to educational and professional tasks was studied. The results of a pilot study to determine the types of social and psychological adaptation are described and the structural indicators of the types are identified. The data on the changes in the level of anxiety, frustration and rigidity under the influence of the program of forming a constructive type of social and psychological adaptation are presented. The depth of the study of the phenomenon of social and psychological adjustment is analysed on the basis of different approaches in the works of Russian and foreign authors who examined the effects of external and internal factors on the success of the adaptation of the person in terms of social well-being, self-aggression, pedagogical support, demographic determinants. These issues are also addressed in the context of the results of development environment, the effectiveness of teaching and research, national identity, in terms of developing didactic methods. The necessity of updating the student’s leadership potential for success in professional activity by adjusting the type of socio-psychological adaptation is grounded. The professional space of the experts in public relations is described and the importance of participation in public education on the issues related to political, economic and social processes of the state, the ruling cabinet, strategic planning of the development of society, creating the political image of the leader of the state is emphasized. The relevance of the experts in the field of public relations in today's dynamically changing social environment is determined including the phenomena of social tension, political conflicts, mass migration due to the global economic crisis.